Pedagogias quilombolas – considerações sobre as possibilidades de uma educação escolar quilombola em Minas Gerais - Leal, Francy Eide Nunes (2021)
This thesis is the result of a collective construction with quilombola educators. It was written through various voices, writings, and bodies, with the focus on problematizing, from na anthropological perspective, processes and situations involving quilombola school education in Minas Gerais (Brazil). The objective was to analyze the elaboration process of the current legislation on the subject, the conflicts arising from and implicit in this process, the institutionalization of the state bureaucracy in Minas Gerais, and the possible advances observable from the “school ground”, such as the elaboration of counter-colonial pedagogical practices, a central element in the thesis. Besides the analysis of secondary data, I also carried out an ethnography in the Fazenda Passagem Funda State School and followed events in which quilombola intellectuals and teachers spoke about the issue. Thus, it became evident that the implementation of “quilombola schools” instead of “schools in the quilombos” requires a long process of community resistance in face of the existing tensions inside the school spaces and territories, which are permeated by foreign policies and values. The progressive overcoming of these tensions, as we have seen, has been occurring with the recognition of quilombola teachers, as a particular category, and the access of quilombolas to universities, which materialize the possibility of building a differentiated quilombola school education – anti-racist, autonomous, counter-colonial, and collectively promoted by the communities.